Rewards & Organizational Creativity: Knowledge Sharing as a Mediator in The Creative Industry in Indonesia - Nursyirwan, Vivi Iswanti; Ardaninggar, Sasmita Sari; Hunein, Hamida; Anggraini, Nova (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
In the era of globalization, creativity is crucial for maintaining and enhancing an organization's competitive advantage, particularly for small and medium enterprises (MSMEs) facing global competition. Organizational creativity, which stems from individual contributions and collaborative processes, leads to innovation. To foster creativity, factors such as rewards and knowledge sharing among employees play a significant role. This research aims to further explore the influence between rewards, knowledge sharing, and creativity, as well as testing the role of knowledge sharing as a mediator variable in this modeling. By better understanding these dynamics, it is hoped that organizations can design more effective reward and knowledge sharing strategies to increase innovation and competitiveness in an increasingly competitive market. This research was conducted at one of the tourism and creative economy associations in Province X, in Indonesia. The researcher chose this research object because the association that is the object of this research is a province X program which is designed to support the potential and progress of micro, small and medium enterprises (MSMEs). The focus of this research is on Small and Medium Enterprises in one of the associations supported by the Department of Tourism and Creative Economy (Parekraf) Province X. The urgency of this research is because the literature related to the study of organizational behavior, especially organizational creativity literature, is still very minimal. The literature reveals more stages that refer more to organizational innovation than organizational creativity. Even though organizational creativity is an important part of forming innovation in an organization. This research offers novelty from a scientific and practical perspective. From a scientific perspective, this research fills the void/gap in previous research literature which is still very minimal. Apart from that, practically this research reveals theoretical studies related to organizational creativity when seen directly in the creative industry. This research uses structural equation modeling to answer the research results. The research results support the research theory, that there is a significant positive influence between rewards, knowledge sharing and organizational creativity.